Pengaruh Model Problem Based Learning (Pbl) Terhadap Peningkatan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Ekonomi - Rini Supreni; Rita Zahara; Bella Anantha Sritumini (Jurnal Pendidikan dan Pembelajaran Ekonomi Akuntansi, 2017)
The purpose of this research is to know the description of the implementation of Problem Based Learning model on Critical Thinking Ability of students on economic subjects. The lack of students' critical thinking skills becomes the background of the problem in this study. Lack of students 'critical thinking skills can be seen from (1) there are still many students emphasizing on the knowledge and understanding aspects of the material (2) more exercises are given to the students' Worksheet (LKPD) or package books. This is caused by several factors one of which is the less effective teachers in choosing the model of learning. The research design used was a non-equivalent control group, with two two groups in this study that is experimental group in the learning using Problem Based Learning model and control group which in learning using conventional learning model. The population in this study is the students of class XI SMA Negeri 25 Bandung, with a sample of two classes. Quantitative data analysis in the form of test is done to the result of pretest and postes of both classes using t-test. Based on the results of research explains that there is the influence of Problem Based Learning model of learning on improving students' critical thinking skills in the eyes of economic pursuit. Improvement of students' critical thinking skills in the economic pursuit of learning using Problem Based Learning model is better than students using conventional learning model.